The influence of marketing competency on capital investment collection and their implications on performance - Hendiarto, R. Susanto; Yulfasha, Yuaneu (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The current problem is that performance is still far below expectations, and while the accumulation of capital investment has not been encouraging, this is presumably because marketing competence is still a concern. This study aims to determine the effect of marketing competence on the accumulation of capital investment and its implications for performance through a case study of the business built by the West Java Chamber of Commerce. The research method applied is a descriptive-analytical survey method, and the sample used is 45 respondents. The variables studied for each respondent are marketing competence, capital investment accumulation, and performance. The type of data collected is primary data. The results of the study indicate that marketing competence has no effect and is not significant for the accumulation of capital investment. the accumulation of capital investment and its significant effect on performance. The implication is that marketing competencies need to be applied programmatically and massively. The object of this research is that the sample of respondents used is still limited to the businesses assisted by the West Java Chamber of Commerce in Bandung; therefore, further research based on more varied sampling with a longer duration is necessary in order to obtain generalizable results.